Latitudinal gradients in genetic diversity and natural selection at a highly adaptive gene in terrestrial mammals. Issue 2 (10th November 2020) - Yiming, Li; Siqi, Wang; Chaoyuan, Cheng; Jiaqi, Zhang; Supen, Wang; Xianglei, Hou; Xuan, Liu; Xuejiao, Yang; Xianping, Li
Abstract : Identifying where high genetic diversity is located across our planet and what factors affect the geographical patterns of genetic variation not only provides important insights into distributions of biodiversity but is also crucial for human health, animal and plant breeding and biodiversity conservation. Recent studies show that genetic diversity at nearly neutral genes decreases from the tropics to the poles in different taxa, mirroring the oldest recognized latitudinal gradient of species richness, yet functional genetic diversity has received little attention at such broad spatial or taxonomic scales. Here, we investigated latitudinal gradients in genetic diversity at a polymorphic exon 2 (MHC II DRB gene, 1515 sequences) of the major histocompatibility complex that confers resistance to parasites in 93 terrestrial mammal species at the global scale. We also estimated the effects of species traits, positive selection and anthropogenic biomes on genetic diversity. We found clear latitudinal gradients in genetic diversity and the presence of positive selection at exon 2. Absolute latitude, the presence of positive selection and body mass are important predictors of within‐species genetic diversity. A higher occurrence of positive selection, faster evolutionary speed or slower drift at low latitudes may shape the latitudinal gradient in the within‐species genetic diversity of the gene. Our results contribute to a greater understanding of how species traits, selection and drift geographically shape functional genetic diversity, broadening the generality of latitudinal biodiversity gradient. The results highlight the importance of conservation at low latitudes.